Effect of solvent plasticization on polypropylene microcellular foaming process and foam characteristics - Kaewmesri W. (2014)
In this research, the effect of crystalline fraction of polypropylene (PP) on cell nucleation behavior was overcome by an introduction of solvent-plasticized step to the microcellular foaming in a solid-state batch-foaming process. Utilizing the plasticization performance of the solvent facilitated the PP to be foamed at the temperatures lower than its melting point with the dramatic development in the cellular morphology of the final foams. In consequence of the heterogeneous cell nucleation sites induction and the crystalline loss, which were induced by solvent, a high cell density (i.e., 109-1010 cells/cm3) was promoted without the cell sacrificing at the elevated temperatures (155 and 165°C) and favorable PP microcellular foams were accomplished. © 2007 Wiley Periodicals, Inc.